Some Notes on the Design, Construction and Performance of the Low-Speed Wind-Tunnel at ITB - Harijono Djojodihardjo (Journal of Mathematical and Fundamental Sciences, 1973)
Abstract. A concise description of the design and construction of the low speed wind-tunnel at Institut Teknologi Bandung and the calculation of its energy losses are presented. Some tests have been undertaken to evaluate its performance, in particular to evaluate the flow pattern at the test-section and the power input for a specific range of wind velocity at the test-section. The maximum velocity achieved at the test-section was 30 m/sec with corresponding Reynolds number of 2 x 104 per cm.  Ringkasan. Konstruksi dan perhitungan kerugian energi  pada terowongan angin kecepatan rendah di ITB diuraikan secara garis besar. Selanjutnya dipaparkan hasil-hasil penilaian performance dari terowongan angin ini, terutama mengenai keadaan aliran pada testsectiondan hubungan antara daya input pada motor dengan kecepatan aliran pada test-section. Kecepatan angin sebesar 30 m/det dapat diperoleh pada test-section, dengan bilangan Reynolds sebesar 2 x 104 per cm model.